Increasing Customer Satisfaction Through Digital Banking Technology Services And Service Quality At Bank Syariah Indonesia Kcp Nganjuk Yos Sudarso - Rizky Natalia Hartanti; Dyah Suswanti Respatiningtyas; Rendi Dwi Apriansa; Wiwin Alief Bachtiar (IAEI, 2023)
The purpose of this research was to provide empirical evidence to determine customer satisfaction in terms of digital services and service quality at Bank Syariah Indonesia KCP Yos Sudarso. This research method was a quantitative research with descriptive method. The population in this study were 93 respondents using a purposive sampling technique using the slovin formula, namely taking informants based on respondents who fit the research objectives with certain criteria from 1250 population to 93 responden. Data collection techniques were obtained by observing, interviewing questionnaires and documentation. Data analysis techniques used to data quality testing, classic assumption testing, and hypothesis testing. The result of the research is that digital technology services have a positive and significant effect on customer satisfaction at BSI KCP Yos Sudarso Nganjuk with a value of 4,412. Furthermore, service quality had a positive and significant effect on customer satisfaction at BSI KCP Yos Sudarso Nganjuk of 4,139. Furthermore, the contribution to the influence of digital technology services and service quality is R 0.834 or 83.4%. which had a very strong level of relationship because it correlation coefficient value in the range of 0.8-1. And for the adjusted R Square value of 0.688 or 68.8%, this indicated that digital technology services and service quality are factors that could affect customer satisfaction by 68.8%.